Contamination and "Self-Cleaning" of Soils, Boarded on the Objects of Automobile and Road Complex, from Petroleum Products. (2017) - Iurchenko, Valentina; Melnikova, Oxana; Mikhaylova, Larysa; Lebedeva, Elena
Abstract: In experimental studies it is found that the petrol stations create the highest specific (based on 1 car traffic) emissions and contamination by petroleum products these pollutants of surrounding areas soils among the objects of the auto-road complex. Activity of soil "self-cleaning" from the petrochemicals depends on the concentration of organic carbon, which increases the activity of soil oxidoreductase enzymes carrying the oxidative degradation of hydrocarbons among the objects of the auto-road complex.